Medical Negligence and Malpractice in Bangladesh: Issues and Legal Remedies (Journal of Surgical Sciences, 2022)
Medical negligence and malpractice are common health issues in Bangladesh. People face various problems in the health service sector of Bangladesh. People get services from government hospitals as well as private hospitals and clinic but services and facilities for health care is not satisfactory. Beside these there are lots of health problems issues in the health services has found and negligence and malpractice are two of them. For these reason legal remedies plays an important role in this regard so that fundamental health service can be ensured and people can get protection of Laws. However, the present health service in Bangladesh is facing some problems like negligence for poor as well as rich people. This paper focuses on all existing health issues and legal remedies of health services and proposes some policy recommendations of how to overcome medical negligence and malpractice of medical professionals.Journal of Surgical Sciences 2022;26(2): 86-90